Production and Characterization of Lipase form Aspergillus oryzae ST11, Immobilization with Magnetic Nanoparticles and Nanofibers, and Application for Biodiesel Production - Pattarapon Paitaid (Prince of Songkla University, 2024)
Doctor of Philosophy (Biotechnology), 2019